Assessing cancer patients' quality of life and supportive care needs: Translation-revalidation of the CARES in Flemish and exhaustive evaluation of concurrent validity. Issue 1 (December 2016) - Schouten, Bojoura; Van Hoof, Elke; Vankrunkelsven, Patrick; Schrooten, Ward; Bulens, Paul; Buntinx, Frank; Mebis, Jeroen; Vandijck, Dominique; Cleemput, Irina; Hellings, Johan
Abstract Background The prevalence of cancer increases every year, leading to a growing population of patients and survivors in need for care. To achieve good quality care, a patient-centered approach is essential. Correct and timely detection of needs throughout the different stages of the care trajectory is crucial and can be supported by the use of screening and assessment in a stepped-care approach. The Cancer Rehabilitation Evaluation System (CARES) is a valuable and comprehensive quality of life and needs assessment instrument. For use in Flemish research and clinical practice, the CARES tool was translated for the Dutch-speaking part of Belgium (Flanders) from its original English format. This protocol paper describes the translation and revalidation of this Flemish CARES version. Methods After forward-backward translation of the CARES into Flemish we aim to recruit 150 adult cancer patients with a primary cancer diagnosis (stage I, II or III) for validation. In this study with a combination of qualitative and a quantitative approach, qualitative data will be collected through focus groups and supplemented by two phases of quantitative data collection: i) an initial patient survey containing questions on socio-demographic and medical data, the CARES and seven concurrent instruments; and ii) a second survey administered after 1 week containing the CARES and supplementary questions to explore their impressions on the content and the feasibility of the CARES. Discussion With this extensive data collection process, psychometric validity of the Flemish CARES can be tested thoroughly using classical test theory. Internal consistency of summary scales, test-retest reliability, content validity, construct validity, concurrent validity and feasibility of the instrument will be examined. If the Flemish CARES version is found reliable, valid and feasible, it will be used in future research and clinical practice. Comprehensive assessment with the CARES in a stepped-care approach can facilitate timely identification of cancer patients' psychosocial concerns and care needs so it can contribute to efficient provision of patient-centered quality care. Trial registration ClinicalTrials.gov:NCT02282696 (July 16, 2014).